New characterizations for differences of composition operators between weighted-type spaces in the unit ball - Chen, C. (Ukrains’kyi Matematychnyi Zhurnal, 2021)
In this paper, we present some asymptotically equivalent expressions to the essential norm of differences of composition operators acting on weighted-type spaces of holomorphic functions in the unit ball of $\mathbb{C}^N$. Especially, the descriptions in terms of $\langle z, ζ\rangle^m$ are described. From which the sufficient and necessary conditions of compactness follows immediately. Also, we characterize the boundedness of these operators.